2022
DOI: 10.3389/fbioe.2022.1026911
|View full text |Cite
|
Sign up to set email alerts
|

Superwettable and injectable GelMA-MSC microspheres promote cartilage repair in temporomandibular joints

Abstract: Temporomandibular disorders (TMD) can be treated by promoting cartilage regeneration with biomaterials. However, there are deficiencies in the infiltration function of bone filler biological materials. In this study, stems cells were loaded onto gelatin methacryloyl (GelMA) hydrogel microspheres endowed with superwettable properties and TGF-β sustained-release function, which can quickly infiltrate the irregular surface of the temporomandibular joint (TMJ) bone defect area and accelerate cartilage healing. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 26 publications
0
36
1
Order By: Relevance
“…This supports the hypothesis that 4 weeks is insufficient for signs of cartilage repair to be manifested. These results contrast our previous mouse study 26 and recent animal studies, 15,16 where condylar cartilage and the subchondral bone layer regeneration were observed. Some potential factors may contribute to this apparent contradiction.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This supports the hypothesis that 4 weeks is insufficient for signs of cartilage repair to be manifested. These results contrast our previous mouse study 26 and recent animal studies, 15,16 where condylar cartilage and the subchondral bone layer regeneration were observed. Some potential factors may contribute to this apparent contradiction.…”
Section: Discussioncontrasting
confidence: 99%
“…At 4 weeks, the defect appeared enlarged with a layer of fibrous tissue on its surface. Yang et al., 16 in a rat TMJOA model, showed significantly greater new bone and cartilage formation of an rBMSCs‐coated GelMA microsphere group compared with the microspheres and the control groups. Micro‐CT results also indicated that the rBMSCs‐coated GelMA microsphere group had denser trabecular bone within the TMJ condyle.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Twelve articles received only one citation [ 11 , 18 , 28 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Ten articles were not cited in Wos-CC [ 27 , 29 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [ 101 ] evaluated in vivo and in vitro the effects of an injection of bone marrow mesenchymal stem cell (BMSC)-derived small extracellular vesicles (BMSC-sEVs) on cartilage reconstruction with a TMJOA model in rabbits and confirmed that the BMSC-sEVs may play an important role in cartilage reconstruction in TMJOA via the autotaxin–YAP signaling axis. [ 49 ] also analyzed in vitro and in vivo the effects of an intra-articular injection of MSCs by placing these cells on the surface of TGFβ-loaded GelMA microspheres in a model of TMJ arthritis bilaterally induced in rats. They concluded that BMSCs-coated microspheres can effectively promote the repair and reconstruction of cartilage defects within the TMJ arthritis.…”
Section: Discussionmentioning
confidence: 99%